Effects of informative and confirmatory feedback on brain activation during negative feedback processing - Woo, Yeon-kyoung; Song, Juyeon; Jiang, Yi; Cho, Catherine; Bong, Mimi; Kim, Sung-il (Frontiers in Human Neuroscience, 2015)
The current study compared the effects of informative and confirmatory feedback on brain activation during negative feedback processing. For confirmatory feedback trials, participants were informed that they had failed the task, whereas informative feedback trials presented task relevant information along with the notification of their failure. Fourteen male undergraduates performed a series of spatial-perceptual tasks and received feedback while their brain activity was recorded. During confirmatory feedback trials, greater activations in the amygdala, dorsal anterior cingulate cortex, and the thalamus (including the habenular) were observed in response to incorrect responses. These results suggest that confirmatory feedback induces negative emotional reactions to failure. In contrast, informative feedback trials elicited greater activity in the dorsolateral prefrontal cortex (DLPFC) when participants experienced failure. Further psychophysiological interaction (PPI) analysis revealed a negative coupling between the DLPFC and the amygdala during informative feedback relative to confirmatory feedback trials. These findings suggest that providing task-relevant information could facilitate implicit down-regulation of negative emotions following failure.